UPAYA MENINGKATKAN MOTIVASI BELAJAR SISWA DALAM PEMBELAJARAN SEJARAH MELALUI MODEL COOPERATIVE TIPE PICTURE AND PICTURE KELAS XI SMA N I KELAM PERMAI KABUPATEN SINTANG - Susi Susanti; Resti Mulyani (Lembaga Publikasi Ilmiah dan Penerbitan (LPIP), 2015)
motivation in learning history through Cooperative models of type Picture and Picture in class XI SMA N 1 Kelam Permai Sintang District?” This study used action research (action research) conducted through two cycles with each cycle stages are planning, action, observation, and reflection. And forms of research that action research (classroom action research). Subjects in this study were students of class XI IPS 3 Kelam Permai Sintang District academic year 2014/2015, amounting to 27 people and 1 subject teachers of history. Data were obtained through classroom observation and documentation of the results of the actions taken and the data about the image, with this action research will note an increase or decrease after the class actions do persiklus. Research result are (1) Students motivation before using the model type Cooperativ Picture and Picture in class XI sejarahdi learning SMA N 1 Kelam Permai Sintang District the percentage of student motivation 57.0% categorized enough this can be seen from the results of pre-action that researchers do. Student motivation before using the model Cooperative Picture and Picture type varies greatly, since most of the students' motivation is still arguably less, because students are more likely to still passive, busy with their own activities and are less motivated to learn, (2) Application of Cooperative models of type Picture and Picture in pemebalajaran history in class XI IPS 3 SMAN 1 Kelam Permai Sintang District has implemented optimally and effectively. It can be seen from the students' motivation where students are more active, the students were interested and enthusiastic to follow the teaching of history. Because learning Cooperative models of type Picture and Picture is a learning model that uses paired images or sorted into order logis, (3)There is an increase in students' motivation in learning history in class XI SMA N 1 Kelam Permai Sintang. This is evident from the average value of student learning ratamotivasi before using the model Cooperative Picture and Picture mode is 57.0% with less category, and after using the model Cooperative type Picture and Picture in the first cycle was 72.4% in the category quite well and then in the second cycle can be obtained average value of students' motivation is at 85.7% categorized either. Means of pre-action to cycle 1 rose to 15.4% and in the second cycle, up 13.3%. It shows that the motivation of students of class XI IPS 3 SMAN 1 Kelam Permai Sintang District after using the model type Picture and Picture Cooperative has increased, as well as student motivation categorized either. Kata kunci: learning motivation, Pembelajaran Sejarah, Model Cooperative Tipe Picture and Picture